Investigating the mechanical properties of Thiel-embalmed metatarsals - Gatt, Alfred (Journal of Medical Biomedical and Applied Sciences, 2016)
Introduction: Fresh-frozen cadaveric samples are often utilized for research and the study of anatomy. Thiel embalming offers the possibility of preserving human tissue and bone without requiring special freezing equipment. Thus mechanically testing Thiel embalmed bone to compare with fresh frozen samples becomes increasingly important.Method: The 1st and 5th metatarsals were harvested from 3 cadavers which had one foot fresh frozen and the other Thiel embalmed. These metatarsals underwent 3-point testing until fracture.Results: 5th metatarsal average fracture force for Thiel embalmed and fresh frozen samples was equal to 305N (SD241N) and 539N (SD232N) respectively. Similarly average fracture force for Thiel embalmed and fresh frozen 1st metatarsals was equal to 614N (SD192N) and 694 (SD273N) respectively.Conclusion: Thiel embalmed metatarsals yield at a lower force than fresh-frozen metatarsals obtained from the same cadaver. Thus one should be cautious about utilizing these preserved bones in situations where bone strength is required.